Description of Basic Gymnastics Floor Movement Skills for Beginner Athletes of Persani Gymnastics Club Malang Regency - Arrosyadi, Muhammad Ilham; Kusmawati, Wiwik; Sudarsono, Sudarsono; Nuh, Fuad Azhar (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to describe the basic movement skills of beginner athletes in practicing floor gymnastics at the PERSANI Gymnastics Club in Malang Regency. The focus of this study is to practice three types of basic floor gymnastics movements, namely forward rolls, backward rolls, and handstands. The method used is quantitative descriptive with data collection techniques through systematic observation using performance assessment sheets. The subjects of the study consisted of four beginner athletes. The results of the study showed that in general the athletes' movement skills were in the good to very good category, although there were still shortcomings such as imperfections in leg straightness during handstands and imperfect landings on backward rolls. This study emphasizes the importance of routine training, technical assistance, and periodic evaluations in the coaching process for beginner athletes to improve their basic movement skills.